The foetal development of lactate dehydrogenase isoenzymes, glucose 6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase from human striated muscle - Clausen, Jørgen (1969)
1. Human foetal skeletal muscles involved in support and in periodic contractility were studied for their content of total extractable lactate dehydrogenase, glucose 6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase activities as well as for the relative distribution of lactate dehydrogenase isoenzymes. 2. During foetal development a linear steady increase in total lactate dehydrogenase activity as well as a linear decrease in the H/M sub-unit ratio of the isoenzymes was found. 3. No significant changes were found in the activities of the enzymes of the hexose monophosphate shunt (C-6 oxidation). 4. The changes found suggest a steady increased synthesis of lactate dehydrogenase M-sub-units in human skeletal muscles during foetal development. 5. The weekly changes in the total lactate dehydrogenase activity and in lactate dehydrogenase isoenzymes are lower in muscles involved in support than in those involved in periodic contractility. 6. These findings, together with the literature available, are consistent with the morphological fact that foetal development of skeletal muscles mostly concerns the white muscle fibres and not the red muscle fibres.